Алхимик: роман / П. Коэльо ; [перевод с португальского А. Богдановского] - Коэльо Пауло (София, 2008)
Экземпляры: ф.9 (20221024) / Инвентарный номер: 62627 / Цена: / Сис.шифр: 84(7Бра)-4 / Авт.знак: К 76 / ГРНТИ: 17.82.31 / ББК: 84(7Бра)-44